Farmer Breeding Objectives and Production Constraint of Arsi Cattle Reared in Mid Rift Valley of Oromia - Aman Gudeto; Sandip Banerjee; Tadele Mirkena (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
The study was conducted in mid-rift valley of Oromia Regional State of Ethiopia with objective to assess traditional cattle breeding objectives and their production constraints. Adami Tulu Jidokombolcha (ATJK), Bora, Dodola, Shala and Negele-Arsi were purposely selected from East Shoa and West Arsi Zones which found in the Oromia Region. The two hundred forty respondents were selected based on random sampling procedures. The main of age and family size of the respondents were 43.1 years and 8.9, respectively. Survey result revealed that family size were higher in Shala where the poly marriage practice was more common than others districts. Cattle population per house hold were higher in Shala while sheep population were higher in Dodola and Bora districts. Goat size were higher in Negele-Arsi, ATJK and Shala districts. Furthermore, finding showed that farmers were reared cattle mainly for draft, milk, risk aversion and income source. The survey result indicated that feed shortage, water scarcity, disease and shortage of improved genotype were the major cattle production constraints in the studied districts. However water shortage was not secondarily critical in Dodola district. Forage improvement, water conservation, disease prevention and improving genetic potential of cattle is needed to solve the main livestock production constraint to improve the livelihood of small holder farmers.